2007
DOI: 10.1111/j.1600-0447.2007.00957.x
|View full text |Cite
|
Sign up to set email alerts
|

The doctrine of the two depressions in historical perspective

Abstract: Objective-To determine if the concept of two separate depressions -melancholia and nonmelancholia -has existed in writings of the main previous thinkers about mood disorders.Method-Representative contributions to writing on mood disorders over the past hundred years have been systematically evaluated.Results-The concept of two separate depressions does indeed emerge in the psychiatric literature from the very beginning of modern writing about the concept of 'melancholia'. For the principal nosologists of psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(59 citation statements)
references
References 25 publications
1
53
0
5
Order By: Relevance
“…This situation is not unique to the palliative care setting, as multitudinous concepts of depression have beleaguered the field of psychiatry over the course of its history [11][12][13] and continue to be actively debated. 13,14 The palliative care setting, however, arguably adds to the ambiguity because of the symptomatic similarities between depression and conditions commonly occurring at the end of life (EOL), such as illness and the dying processes and the attendant emotions in this context. 15,16 Health professionals have reported difficulties with assessing and managing depression in the palliative care setting.…”
mentioning
confidence: 99%
“…This situation is not unique to the palliative care setting, as multitudinous concepts of depression have beleaguered the field of psychiatry over the course of its history [11][12][13] and continue to be actively debated. 13,14 The palliative care setting, however, arguably adds to the ambiguity because of the symptomatic similarities between depression and conditions commonly occurring at the end of life (EOL), such as illness and the dying processes and the attendant emotions in this context. 15,16 Health professionals have reported difficulties with assessing and managing depression in the palliative care setting.…”
mentioning
confidence: 99%
“…For example, experienced psychiatrists always considered that MDD could be categorized between a biological, "endogenous" depression-called melancholic depression-and a psychogenic, "exogenous" depression-called non-melancholic depression [16,17]. This perception is supported by controversial evidences that melancholic patients would have genetic and biological determinants; more severe symptomatology; more evidence of neurobiological abnormalities, especially of the hypothalamic-pituitary-adrenal axis; low response to placebo; and superior response to pharmacological and electroconvulsive therapies [5,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, there has been extensive discussion on whether non-melancholic and melancholic depression are two separate conditions or reflect differences in the severity of a single syndrome. 6,7 In the section concerning mood and affective disorders of the [6][7][8][9][10][11][13][14][15]18 (see Table 2 26 Calil, in a non-systematic review, examined the Latin American concept of depression and presented a Brazilian proposal. 27 27,28 Banzato, in a non-systematic review, investigated classification issues in psychiatry: the move towards the ICD-11 and DSM-V. 29 The 30 10,36 In the 1990s, however, several studies found that the sensitivity of the DST for the diagnosis of the melancholic subtype of major depression as defined by the DSM-III was low (35-45%), although its specificity was high (70-89%).…”
Section: The Results Of Classification Efforts In the 1980s And Earlymentioning
confidence: 99%